Identification of Potential Maintainer and Restorer Lines Using Testcross Hybrids - Mohammad Amir Hossain; Md. Jamil Hasan; Mosammat Umma Kulsum; Md. Mahathir Sarker (Turkish Journal of Agriculture: Food Science and Technology)
Five CMS lines were crossed with 49 genotypes as ‘testers’ to get 245 hybrids. The 245 hybrids were subjected to pollen and spikelet fertility analysis. Among the 245 hybrids 21 hybrids were expressed as restorers, 24 as maintainers, and 200 intermediate types. Six tester’s viz., BR6592-4-6-4, BR6839-41-5-1, IR74052-184-3-3, IR72593-B-3-2-2-2, BR7011-37-1-2, and IR72049-B-R-22-3-1-1 were identified as restorers for highest 2 lines out of the five CMS lines, differently. None of them were found to be restorer for all the five CMS lines. BAU581 was found to be maintainer for four lines except for D.ShanA. Purbachi was found to be maintainer for three lines except for D.ShanA and IR73328A out of the five CMS lines. Out of 245 crosses only 45 crosses contributed directly to the identification of maintainer and restorer. Other crosses were more or, less of intermediate types which indicated neither maintainer nor restorer. It is well known that, pollen fertility is controlled by one dominant gene (RfRf). If pollen fertility is governed by only one gene the product would be either restorer or, maintainer where will be no existence of intermediate types. So, there might be modifier genes in different genotypes which interacted with male sterile nuclear genes that resulted in intermediate male sterility in the crosses.